2021
DOI: 10.1186/s13063-021-05123-w
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber and probiotics for the treatment of atypical antipsychotic-induced metabolic side effects: study protocol for a randomized, double-blind, placebo-controlled trial

Abstract: Background Atypical antipsychotic medications, which are effective for the treatment of schizophrenia and bipolar disorder, are associated with features of metabolic syndrome, such as weight gain, hyperglycemia, dyslipidemia, and insulin resistance. Although there are a few studies on the effects of dietary fiber or probiotics on weight loss in obese people, no published trials have reported the efficacy of dietary fiber and probiotics on reducing atypical antipsychotic-induced weight gain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“… 90 Currently, a prospective study using a combination of probiotics (combination of Bifidobacterium , Lactobacillus , and Enterococcus ) and prebiotic (dietary fiber – maltodextrin and Perfect dietary fiber drink) formulations in 100 patients receiving SGAs with >10% weight gain is underway. 87 This study will prove insightful in understanding the role of probiotic and prebiotic supplementation in SCZ patients including its effect on weight gain, metabolic syndrome parameters, appetite, and GMB composition. 87 …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“… 90 Currently, a prospective study using a combination of probiotics (combination of Bifidobacterium , Lactobacillus , and Enterococcus ) and prebiotic (dietary fiber – maltodextrin and Perfect dietary fiber drink) formulations in 100 patients receiving SGAs with >10% weight gain is underway. 87 This study will prove insightful in understanding the role of probiotic and prebiotic supplementation in SCZ patients including its effect on weight gain, metabolic syndrome parameters, appetite, and GMB composition. 87 …”
Section: Resultsmentioning
confidence: 96%
“… 87 This study will prove insightful in understanding the role of probiotic and prebiotic supplementation in SCZ patients including its effect on weight gain, metabolic syndrome parameters, appetite, and GMB composition. 87 …”
Section: Resultsmentioning
confidence: 96%
“…The analyses were performed using the Statistical Package for Social Sciences, version 25.0 (SPSS Inc., Chicago, Illinois). A statistical analysis plan was published before in the protocol [ 21 ]. For participants with at least one follow-up visit (118 of 136), the last-observation carried-forward method (intention-to-treat analysis) was employed for efficacy analysis, and all the randomized 136 patients were included for safety analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Written informed consents were obtained from all participants before undergoing examinations. The detailed study protocol has been published previously [ 21 ]. Trial registration clinicaltrials.gov Identifier: NCT03379597.…”
Section: Methodsmentioning
confidence: 99%
“…Yang et al reported that the addition of probiotics, including Bifidobacterium and Lactobacillus, was not sufficient to reduce weight gain in patients with schizophrenia, nor did it significantly improve lipid profiles (Yang et al, 2021). In comparison, the combined use of probiotics and dietary fiber was effective in reducing olanzapine-induced weight gain without any apparent adverse effects while maintaining the desired psychopathological effect (Liu et al, 2021;Huang et al, 2022a;Huang et al, 2022b). Therefore, more randomized controlled trials in humans are needed to translate beneficial findings in animals.…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%